PENGARUH LATIHAN BALLNASTIC TERHADAP KETERAMPILAN MENGGIRING BOLA PADA PEMAIN SEKOLAH SEPAK BOLA WONER 2012 KELOMPOK USIA 15 TAHUN PEKANBARU - Restu Yendri Syaputra; Ardiah Juita; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The problem in this study is that the players lack the ability to dribbleboth in training sessions and in matches. Foot contact when dribbling is not right so theball is out of control. The distance between the player and the ball is too far so that it iseasy for the opponent to grab it. Incorrect body position when dribbling the ball. Whendribbling the ball, the position of the foot and the movement that looks still stiff so that itis less than perfect when dribbling the ball. When dribbling the ball cannot changedirection quickly when passing the opponent. The purpose of this study was to determinethe effect of Ballnastic training on dribbling skills in Woner 2012 soccer school players inthe 15-year-old Pekanbaru age group. The method used in this research is theexperimental method. The research design carried out in this study was